2016
DOI: 10.1080/02640414.2016.1226509
|View full text |Cite
|
Sign up to set email alerts
|

Doping in sport: an analysis of sanctioned UK rugby union players between 2009 and 2015

Abstract: To inform anti-doping policy and practice, it is important to understand the complexities of doping. The purpose of this study was to collate and systematically examine the reasoned decisions published by UK Anti-Doping for doping sanctions in rugby union in the UK since the introduction of the 2009 World Anti-Doping Code. Case files were content analysed to extract demographic information and details relating to the anti-doping rule violation (ADRV), including individuals' explanations for how/why the ADRV oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 15 publications
2
43
0
1
Order By: Relevance
“…We investigated self-other divergence in judgments about doping by athletes competing in a sport at high-risk for doping. In line with rugby's history of relatively high incidence of anti-doping rule violations (Till et al, 2016;WADA, 2018;Whitaker & Backhouse, 2017), estimates of doping likelihood, both self-and other-referenced, were notably higher in our sample of rugby players compared to a mixed sample of individual and team sport athletes (cf., Ring, et al, 2019b). The current study compared self-referenced and other-referenced measures of doping likelihood and guilt, and then examined direct, indirect and conditional effects of perspective on doping likelihood.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We investigated self-other divergence in judgments about doping by athletes competing in a sport at high-risk for doping. In line with rugby's history of relatively high incidence of anti-doping rule violations (Till et al, 2016;WADA, 2018;Whitaker & Backhouse, 2017), estimates of doping likelihood, both self-and other-referenced, were notably higher in our sample of rugby players compared to a mixed sample of individual and team sport athletes (cf., Ring, et al, 2019b). The current study compared self-referenced and other-referenced measures of doping likelihood and guilt, and then examined direct, indirect and conditional effects of perspective on doping likelihood.…”
Section: Discussionsupporting
confidence: 70%
“…Doping may be a problem in contact sports such as rugby where the players' mass, strength and endurance confer performance benefits (e.g., Till, et al, 2016). Although sanctions handed down to elite professional players make the news media, most anti-doping rule violations among rugby players in the UK have been detected in amateur players, with those aged 18-25 years being most at risk for doping (Whitaker & Backhouse, 2017). Accordingly, we chose to recruit young adult amateur club players.…”
mentioning
confidence: 99%
“…Research on AD knowledge has been reported from various viewpoints: competitive characteristics [ 1 , 11 ], athletes who have violated AD rules in the past [ 12 ], cross-sectional and longitudinal investigations [ 13 , 14 ], and competitors’ age [ 15 , 16 ]. There have also been surveys addressing AD knowledge among ASP, such as healthcare professionals and coaches [ 17 – 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unintentional doping (also known as ‘inadvertent’ or ‘accidental’ doping) refers to the accidental consumption of performance-enhancing substances included on WADA’s banned list 1. It often occurs when an athlete uses a product (eg, nutritional supplements, ‘energy’ drinks or products, and medical, herbal or ‘natural’ products) that contains the banned substance or is exposed to the banned substance in routine situations (eg, drug smoke, hormone-tainted meat), while being unaware of the presence of the banned substance 1-4. However, it is acknowledged that unintentional doping is often used as an excuse by athletes to explain adverse analytical findings in doping control samples 4.…”
mentioning
confidence: 99%
“…It often occurs when an athlete uses a product (eg, nutritional supplements, ‘energy’ drinks or products, and medical, herbal or ‘natural’ products) that contains the banned substance or is exposed to the banned substance in routine situations (eg, drug smoke, hormone-tainted meat), while being unaware of the presence of the banned substance 1-4. However, it is acknowledged that unintentional doping is often used as an excuse by athletes to explain adverse analytical findings in doping control samples 4. WADA has adopted a near zero-tolerance policy when it comes to athletes claiming unintentional use.…”
mentioning
confidence: 99%